A Catalyst-Free Synthesis of Fused Perfluoroalkylated 2,3-Dihydroisoxazoles via Oxa-Michael-Aldol Annulation - Zhou, Wei; Yao, Lan; Liu, Yongxiurong; Shen, Lichun; Chen, Jie; Deng, Hongmei; Shao, Min; Zhang, Hui; Tang, Xiaojun; Cao, Weiguo (Synthesis, 2021)
A novel synthesis of fused perfluoroalkylated 2,3-dihydroisoxazoles is achieved via oxa-Michael-aldol annulation between perfluoroalk-2-ynoates and N-hydroxyimides. This method provides a convenient route for the synthesis of pyrrolidin-2-one-fused perfluoroalkylated 2,3-dihydroisoxazoles in yields of up to 97%. Diverse and pharmaceutically attractive polycyclic scaffolds can be obtained rapidly and efficiently under these mild, catalyst-free conditions.
Keywords: dihydroisoxazoles; piperidin-2-ones; perfluoroalkylated; oxa-Michael-aldol annulation; catalyst-free conditions